Determinants of Qris Use and Imports in Generation X in Bali Province - Annastasya, Jihan Wilanda; Setyari, Ni Putu Wiwin (CV. Rayyan Dwi Bharata, 2025)
Quick Response Code Indonesian Standard or QRIS is one of the strong attractions in the midst of financial system transformation implemented by the government and business actors. However, the number of QRIS users is only dominated by Generation Z and Generation Y who are familiar with technology compared to Generation X. The determinants of QRIS use and imports for Generation X in Bali Province are easy, safe and useful. This study aims to analyse easy, safe, benefits directly on the use of QRIS as well as to analyse easy, safe, benefits and the use of QRIS directly on imports and to analyse easy, safe and indirect benefits on imports through the use of QRIS in Generation X in Bali Province. The type of data in this study is primary data in the form of quantitative obtained from the results of the questionnaire. This research was conducted in Bali Province with 100 respondents. The data analysis technique used is Path Analysis. The results showed that ease and benefits had a direct effect, while safety had no direct effect on the use of QRIS in Generation X in Bali Province. Safe and QRIS usage have a direct effect, while easy and benefits have no direct effect on imports in Generation X in Bali Province Easy and benefits have an indirect effect, while safe has no indirect effect on imports through the use of QRIS in Generation X in Bali Province. The implication of this research is that ease and benefits are the main drivers for Generation X in Bali Province in using QRIS. Safe is not considered an important factor for Generation X in Bali Province in using QRIS. Increasing the safe factor and the use of QRIS can directly increase the value of imports for Generation X in Bali Province. The perceived ease and benefit factors are not strong enough to directly influence the import decision of Generation X in Bali Province. Easy and benefits are the main reasons for Generation X in Bali Province to import through the use of QRIS. Safe is not considered a major factor for Generation X in Bali Province, due to the trust that has been built regarding security in import transactions through the use of QRIS.